Primitive Neuroectodermal Tumor (PNET) at the Level of Thoracic Spine: A Case Report - Magetsari Rahadyan (Journal of Global Pharma Technology, 2016)
Introduction Primitive neuroectodermal tumors (PNET) are malignant tumors thought to arise from the neural ectoderm and comprise of undifferentiated small round cells that affect soft tissue and bone. These tumors occur primarily in children and adolescents (thirteen to sixteen years old), with a tendency to recur quickly and metastasize especially to lungs, bone marrow, brain and lymph nodes. PNET are uncommon malignancies that are increasingly reported in the literature and located in the spine are extremely rare. In this study we present a case of 14 years old girl with PNET of the thoracic spine which recur after initial resection. Case Report a 14 years old girl presented with low back pain and progressive weakness of both of lower limbs of three months duration. On physical examination, motor and sensory function was lost, motoric strength in the lower limbs was grade 1/5 with hypoesthesia below L1 level. Magnetic resonance imaging (MRI) of the spine showed burst pathologic fracture of the 12th thoracic spine with suspicious malignant lesion in the 12th thoracic spine. Initially the condition was treated with laminectomy, decompression, stabilization and open biopsy. Histopathology and immunohistochemistry of the lesion revealed the diagnosis of PNET. During the early postoperative course, she had instance neurological recovery and was able to walk unassisted. But, 1 month later the neurologic deficit recurred and she was treated with extended laminectomy with tumor debulking. Then the patient received chemotherapy and planned for radiotherapy. Conclusion Primitive neuroectodermal tumors (PNET) are extremely rare and are aggressive with poor outcomes. Good modalities play a significant role in the identification of the feasibility of surgical excision of the tumors, detection of distant metastasis, and evaluation of the efficacy of therapeutic interventions.Keywords: Primitive neuroectodermal tumor (PNET), Malignant Tumor, Rare Tumor, Spinal Tumor.